REPRESENTASI PEREMPUAN DALAM MEME MEDIA SOSIAL: PERSPEKTIF FEMINISME SIMONE DE BEAUVOIR TERHADAP STEREOTIP GENDER - Safitri, M.Pd., Nur Anita Syamsi; Humaira, Annisa Nur Afiat (Universitas Negeri Makassar, 2025)
This study aims to analyze the representation of women in social media memes through the lens of Simone de Beauvoir’s existentialist feminism. In the digital context, memes function not only as entertainment but also as a medium for disseminating ideology also gender stereotypes that often disadvantage women. This study employs a qualitative method with a descriptive approach. The material objects are memes circulating on social media, while the formal object is Beauvoir's feminist concept that positions women as autonomous subjects rather than